Edukasi Patient Safety pada Pasien dan Keluarga Pasien di Instalasi Poliklinik Rumah Sakit Umum Daerah Sayang Rakyat Kota Makassar: Patient Safety Education for Patients and Their Families in the Polyclinic Installation of Sayang Rakyat General Hospital, Makassar city - Rini Rachmawaty; Firdaus Hamid; Indra Gaffar; Andi Baso Tombong; Poppy Nurul Asmaul Razak; Fatima Angraini (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
In 2019, data was obtained that there were 12 cases of Potential Injury Events (KPC) at RSUD Sayang Rakyat. Therefore, RSUD Sayang Rakyat is the target of Patient Safety Education activities for patients and their families at the Polyclinic. The aim of carrying out community service is to prevent and reduce risks, errors and losses that occur to patients during the provision of health services. This community service uses educational methods for polyclinic patients and families using video and flayers and is simulated directly to patients and families. Besides that, to measure patient and family understanding before education, they are given a pre-test and after education, it is given a post-test which consists of 6 multiple choice questions related to 6 patient safety goals in the hospital. The evaluation results obtained after 3 times of education showed significantly increased knowledge of patients and patient families compared to before education with values 0,529 (p= 0,041) in education 1, 0,8 (p=0,046) in education 2 and 0,692 (p=0,041) in education 3 it is hoped that hospitals will pay more attention to and improve patient safety in hospitals in order to prevent incidents to patients.